Reconstructing Language Tests: A Comparative Study for Improved Assessment - Ikrimah, Ikrimah; Asi, Natalina (Universitas Lancang Kuning, 2024)
In the realm of educational systems, language testing plays a vital role in assessing a learner's language abilities. Ensuring the reliability and validity of such tests is crucial to provide an accurate gauge of proficiency and depth of learners' knowledge. However, modifications are necessary for testing methods to cope with the ever-evolving landscape of teaching methodologies while maintaining their effectiveness. This study employs a comparative analysis approach between an original and a reconstructed English language test, following the guidelines of the 'Kurikulum Merdeka' for 11th-grade students. Utilising Bloom's Taxonomy as a framework, both the original and reconstructed tests are evaluated with respect to cognitive complexity and coverage of various cognitive skills. The implemented modifications in the test demonstrated a significant enhancement in the overall effectiveness and alignment with broader cognitive skills. Two key modifications, expanding the multiple-choice answers from four to five and realigning questions to span various cognitive levels as per Bloom's Taxonomy, were found to be effective in increasing the complexity and scope of the test. This, in turn, led to a more comprehensive engagement of students in the test. The study concludes that the reconstructed test format, when compared to the original, offers a more effective overall assessment structure. Its more challenging nature stimulates critical thinking, deep understanding, and creativity among learners, thereby promoting improved language assessment and a better understanding of teaching-learning processes. It underscores the necessity of periodic improvements and modifications in test designs, ultimately contributing towards more precise and effective language testing.